Influence Pedagogical and Professional Competence Towards Improving the Quality of Education at SMA Negeri 1 Payaraman - Sugiyarto Sugiyarto; Nur Ahyani; Mahasir Mahasir (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to determine the influence of pedagogical and professional competencies on improving the quality of education at SMA Negeri 1 Payaraman. The research employed a quantitative approach with a correlational design. Data were collected through questionnaires distributed to teachers and analyzed using statistical methods to test the relationship between the variables. The findings indicate that both pedagogical and professional competencies have a significant and positive influence on the quality of education. Pedagogical competence, which encompasses the ability to design, implement, and evaluate learning processes, contributes to more effective teaching strategies. Meanwhile, professional competence, including mastery of subject matter and continuous professional development, supports academic excellence and student achievement. The results suggest that enhancing teachers' competencies in these areas is essential for improving educational quality. Therefore, educational stakeholders are encouraged to invest in continuous training and development programs for teachers.